The Justice in International Law: A Study from the Perspective of Immanuel Kant - Yuliastini, Anita (Faculty of Law, Universitas Pekalongan, 2024)
This article examines the concept of justice in international law through the perspective of Immanuel Kant, highlighting the application of universal moral principles and the categorical imperative in relations between states. Kant argued that justice should be understood as a principle that applies to all human beings without exception, requiring states to act in a manner that promotes individual freedom without harming the freedom of others. In the context of international law, this includes respect for human rights, the responsibility of states to other states, and the formation of a federation of states that work together to achieve global peace and justice. The article also discusses the relevance of Kant's thinking in the modern international legal system, where international institutions such as the United Nations, the International Court of Justice, and the International Criminal Court play a role in upholding the principles of justice and peace. Thus, Kant's theory makes an important contribution to the formation of an international law that is just, inclusive, and based on a universal morality that respects human freedom and rights